Law Students’ Perceptions on a Professional Writing Activity: Inclusivity and the Changing Concept of Employability - Canto-Lopez, Maribel (Revista Jurídica de Investigación e Innovación Educativa (REJIE Nueva Época), 2025)
Higher Education is changing in the United Kingdom and internationally. The increased commercialisation and massification of the sector over the years has brought the pressure on university students’ employability. Admittedly, as the body of university’ students is growing and diversifying, the activities design to embed employability in the curriculum need to have inclusivity in mind, to support students despite their non-traditional background. In this landscape, this article explores students’ perception on a professional writing activity set in a core module, in the second year of their Law Degree. The study used qualitative research (n=35) and was conducted in a UK research-intensive institution. The results of this work suggest the need for universities and law teachers to hear the diverse voices of their students, who in this project, acknowledged the benefits of introducing experiential employability activities in their core modules with links to a real employer. In the one hand, law students are motivated to experience something different in their curriculum. In the other hand, all the students feel valued and included in the employability activity, even those considered to be non-traditional. If we acknowledge and value the diversity of our students, we may help them reach the future they all deserve.